2020
DOI: 10.33210/ca.v9i3.352
|View full text |Cite
|
Sign up to set email alerts
|

Percepción docente sobre la educación a distancia en tiempos de COVID-19

Abstract: INTRODUCCIÓN. La pandemia Covid-19 ha obligado a las instituciones educativas de todo el mundo a cambiar su modalidad de enseñanza, y pasar de un modelo mayormente presencial a otro donde la virtualidad presenta mayor protagonismo. OBJETIVO. Conocer la percepción de los docentes acerca de la educación a distancia durante la pandemia Covid-19 en una institución educativa estatal de Lima, Perú. MÉTODO. Estudio descriptivo transversal, con una muestra de 53 docentes en quienes se aplicó un cuestionario de 36 ítem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 5 publications
0
3
0
10
Order By: Relevance
“…However, they reported that WhatsApp was the main tool for the development and organization of synchronous classes. Other studies agree that WhatsApp was the main means of communication between students and teachers during the development of classes (Santos et al, 2020;Mishra et al, 2020;Ferri et al, 2020;Fernández et al, 2020;Baptista Lucio et al, 2020). In the case of Baptista Lucio et al, (2020) the researchers highlight that although WhatsApp is the main communication tool between teachers and students, Facebook, Messenger, and phone calls are also used according to the school level of the students.…”
Section: Discussionmentioning
confidence: 97%
“…However, they reported that WhatsApp was the main tool for the development and organization of synchronous classes. Other studies agree that WhatsApp was the main means of communication between students and teachers during the development of classes (Santos et al, 2020;Mishra et al, 2020;Ferri et al, 2020;Fernández et al, 2020;Baptista Lucio et al, 2020). In the case of Baptista Lucio et al, (2020) the researchers highlight that although WhatsApp is the main communication tool between teachers and students, Facebook, Messenger, and phone calls are also used according to the school level of the students.…”
Section: Discussionmentioning
confidence: 97%
“…However, the same authors reported that there was minimal use of WhatsApp among teachers and students whereas text messaging and videoconferences, social networks, and telephone calls were used as the main means of communication. On the other hand, Santos et al (2020) reported the massive use of WhatsApp among teachers as well as the minimum use of educational platforms for communication purposes.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of technological resources along with a space to study has deeply impacted students, especially those from a lower socio-economic status (Cabero & Valencia, 2021;Adedoyin & Soykan, 2020). In education, research has confirmed time and again that major challenges faced by the education community are lack of resources and infrastructure (Zhang et al, 2020), lack of reliable internet connection (Xie et al, 2020;Cesco et al, 2021;Tabassum et al, 2021;Hebebci et al, 2020;Lapada et al, 2020;Yusuf & Ahmad, 2020), insufficient digital literacy among teachers and students (Almazova et al, 2020;Adedoyin & Soykan, 2020), lack of and the need of training in the use of technological tools (Santos et al, 2020;Yusuf & Ahmad, 2020) and lately, socio-emotional and stress factors affecting students and teachers (Hadar et al, 2020;Marsollier & Expósito , 2021;Lapada et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…La percepción docente se ha estudiado desde diferentes ámbitos de interés, por ejemplo, en torno a las actividades y el burnout (Oliveira et al, 2021), la gestión (Changanaqui & Huapaya, 2017), el uso de herramientas como las Tecnologías de la Información y la Comunicación (TIC), siendo este último un tema destacado (Álvarez, 2020;Garita-González, Gutierrez-Durán & Godoy-Sandoval, 2019). Con motivo de la pandemia por la COVID-19, las actividades educativas tuvieron una transformación radical, la cual alteró la percepción docente en cuanto a su labor (Santos et al, 2020), manifestando las dificultades presentes en la educación a distancia, además de la preocupación por la poca formación adquirida.…”
Section: Revisión De La Literaturaunclassified